2021
DOI: 10.1177/23259671211015973
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Femoroacetabular Impingement in Patients With and Without Borderline Developmental Dysplasia of the Hip: A Systematic Review and Meta-analysis

Abstract: Background: Based on previous studies, it is difficult to discern whether patients who have femoroacetabular impingement (FAI) with borderline developmental dysplasia of the hip (BDDH) would benefit from arthroscopy when compared with patients without BDDH. Purpose: To evaluate the existing comparative literature on arthroscopic findings, procedures, patient-reported outcomes (PROs), and failures in patients who have FAI with BDDH compared with those without BDDH. Study Design: Systematic review; Level of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In our meta-analysis, all six identified studies used LCEA as the radiographic marker for BDH, with 25° being the cutoff point for BDH. This is in line with the results of Murata et al 6 where all studies included had the same cutoff point. By contrast, the cutoff point between BDH and frank dysplasia were more unclear, with some studies using a cutoff of less than 18° 2022 while other studies used a cutoff point of less than 20°.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our meta-analysis, all six identified studies used LCEA as the radiographic marker for BDH, with 25° being the cutoff point for BDH. This is in line with the results of Murata et al 6 where all studies included had the same cutoff point. By contrast, the cutoff point between BDH and frank dysplasia were more unclear, with some studies using a cutoff of less than 18° 2022 while other studies used a cutoff point of less than 20°.…”
Section: Discussionsupporting
confidence: 91%
“…17,18 Future investigations should explicitly define upper and lower bounds when defining borderline dysplastic and normal coverage populations, given the existence of more extreme populations such as frank dysplasia or pincer deformity. Although this meta-analysis highlights that the LCEA is currently the benchmark for radiographically identifying BDH, 5,6 some have suggested alternate radiographic measurements, such as the Femoro-Epiphyseal Acetabular Roof Index, as either an alternative or adjunctive measure for assessing BDH. 34 The present review passively identified only two studies relating Femoro-Epiphyseal Acetabular Roof Index to PROs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2019 to 2021, after eliminating duplicate literature, 29 studies were selected from four systematic reviews of BDDH. [3][4][5][6] Of these, LCEA was used to define BDDH in 28 studies, and one used LCEA combined with Sharp angle and ACEA; 14 studies reported the LCEA range of 20°to 25°, 10 reported 18°to 25°, and four reported <25°. Additionally, 18% of hip dysplasias showed a change in pelvic tilt of >10°on radiographs from supine to standing.…”
Section: Definition Of Bddhmentioning
confidence: 99%
“…Studies have shown that the average difference between Wiberg's and Ogata's methods for measuring LCEA is about 4°. From 2019 to 2021, after eliminating duplicate literature, 29 studies were selected from four systematic reviews of BDDH [3–6] . Of these, LCEA was used to define BDDH in 28 studies, and one used LCEA combined with Sharp angle and ACEA; 14 studies reported the LCEA range of 20° to 25°, 10 reported 18° to 25°, and four reported <25°.…”
Section: Definition Of Bddhmentioning
confidence: 99%